The relationship between safety behaviour and safety awareness among Larut Matang and Selama district health staffs - Nedunsoleon, Presennah (2021)
Numerous studies have revealed that safety awareness reflects employee behaviour towards and attitude towards safety practice at the workplace. Safety behaviour had been explained by safety compliance and safety participation. The aim of this study is to examine the relationship between safety behaviour and safety awareness. Self administrative questionnaire was applied for data collection which involve 200 health staffs. The raw data were analysed by Statistics Package Social Science (SPSS) Version 25. Safety awareness has been explained by safety behaviour nearly 34%. The safety awareness element need to be considered to increase safety behaviour towards safety at the work place. Thus, safety knowledge and safety motivation need to be taken account in training curriculum development